LEGAL CONSEQUENCES AGAINST Default in USING THE SPAYLATER FEATURES ON THE SHOPEE APPLICATION - Elvira Fitriyani Pakpahan; Febriyana Laia; Torry Hia (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
In this pandemic era, our mobility and range as a human being is getting smaller. Luckily we are now live in a digital world where everything can be done online. Such as shopping for daily necessities can also be done online. The payment options provided are also quite a lot. One of them is pay later. One of the marketplaces that provides this option is Shopee with the SPayLater service. To explore what are the legal consequences of default in the use of SPayLater services, legal arrangements regarding FinTech and how to minimize the occurrence of misuse of SPayLater services by using normative juridical research methods is the main goal of this study. Based on the results of this study, that there are still a lot of individuals who actually do not comprehend if this SPayLater service is a binding agreement. If there is misuse or Negligence in its use, it can be penalized. As a result, users feel disadvantaged because they get a fairly large fine compared to their actual purchases.